Percutaneous ablation or minimally invasive partial nephrectomy for cT1a renal masses? A propensity score‐matched analysis. (11th December 2021) - Bianchi, Lorenzo; Chessa, Francesco; Piazza, Pietro; Ercolino, Amelio; Mottaran, Angelo; Recenti, Dario; Serra, Carla; Gaudiano, Caterina; Cappelli, Alberta; Modestino, Francesco; Golfieri, Rita; Bertaccini, Alessandro; et al.
Abstract : Objective: Local tumor ablation to treat small renal mass is increasing. The aim of the present study was to compare oncologic outcomes among patients with T1 renal mass treated with partial nephrectomy and local tumor ablation. Methods: To reduce the inherent differences between patients undergoing laparoscopic or robot‐assisted partial nephrectomy ( n  = 405) and local tumor ablation ( n  = 137), we used a 1:1 propensity score‐matched analysis. Local tumor ablation consisted of radiofrequency ablation and cryoablation. Disease‐free survival, overall survival and other causes mortality‐free survival rates were estimated using the Kaplan–Meier method. Multivariable logistic regression and competing‐risk regression models were used to identify predictors of complications, recurrence and other causes mortality, respectively. Results: Partial nephrectomy had higher disease‐free survival estimates, as compared with local tumor ablation (92.8% vs 80.4% at 5 years, P  = 0.02), with no significant difference between radiofrequency ablation and cryoablation ( P  = 0.9). Ablation showed comparable overall survival estimates to partial nephrectomy (91% vs 95.8% at 5 years, P  = 0.6). The 5‐year recurrence rates were 7.9% versus 23.8% for patients aged ≤70 years, and 2.5% versus 11.9% for patients aged >70 years treated with partial nephrectomy and ablation, respectively; the 5‐year other causes mortality rates were 0% and 2.2% for patients treated with partial nephrectomy and ablation aged ≤70 years, and 3% versus 10.9% for patients aged >70 years treated with partial nephrectomy and ablation, respectively. At multivariable analysis, ablation was associated with fewer complications (odds ratio 0.41; P  = 0.01). At competing risks analysis, age (hazard ratio 0.96) and ablation (hazard ratio 4.56) were independent predictors of disease recurrence (all P  ≤ 0.008). Conclusions: Local tumor ablation showed a higher risk of recurrence and lower risk of complications compared with partial nephrectomy, with comparable overall survival rates.